The economics of inflation : a study of currency depreciation in post-war Germany - Bresciani-Turroni, Costantino; Sayers, Millicent E. (London : G. Allen & Unwin, 1937)
The book is a study of currency depreciation in post - war Germany. The financial convulsion of the great depression were in part at least the product of the distortions of the system of international borrowing and lending to which its ravages had given rise. It destroyed the wealth of the more solid elements in German society and it left behind a moral and economic disequilibrium apt breeding ground for the disasters which have followed.
"The Italian original Le vicende del marco tedesco, first published ... 1931. First published in English 1937, the English edition has been substantially revised by the author."
Includes bibliographic references and index
opc 10/02/2015, usc 14/05/2018
Loans
Keywords: Inflation (Finance); Currency question; Inflation - currency depreciation; Germany